2010
DOI: 10.1086/652443
|View full text |Cite
|
Sign up to set email alerts
|

Transmission ofStreptococcus pneumoniaein Rural Gambian Villages: A Longitudinal Study

Abstract: BACKGROUND. To prepare for national introduction of a pneumococcal vaccine of restricted valency, we studied the pattern of nasopharyngeal carriage of Streptococcus pneumoniae and its transmission in Gambian villages over time. METHODS. We collected nasopharyngeal swab specimens every 2 weeks from 158 villagers in 19 households in 2 villages over 1 year. We studied the prevalence and duration of S. pneumoniae carriage, the effect of household size and composition on carriage, and sequence type-specific carriag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
70
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 27 publications
13
70
2
Order By: Relevance
“…Analysed factors included in the multivariate analysis were: age, gender, passive smoking, PD schools attendance, day-care centre (DCC) prior to preschool attendance, family size and PCV7 status. Studies on S. pneumoniae acquisition and clearance show a mean duration of carriage ranging from 2 to 10 weeks [20]. In our study, the inter-sampling period was approximately 12 weeks.…”
Section: Discussionmentioning
confidence: 65%
“…Analysed factors included in the multivariate analysis were: age, gender, passive smoking, PD schools attendance, day-care centre (DCC) prior to preschool attendance, family size and PCV7 status. Studies on S. pneumoniae acquisition and clearance show a mean duration of carriage ranging from 2 to 10 weeks [20]. In our study, the inter-sampling period was approximately 12 weeks.…”
Section: Discussionmentioning
confidence: 65%
“…Studies in several African countries have shown that the proportion of children with nasopharyngeal carriage of S. pneumoniae and H. influenzae far exceeds that of adults, with pneumococcal carriage exceeding 90% in some studies. [21][22][23][24] Because of their childcare role, females have frequent direct exposure to these nasopharyngeal organisms, which likely increases their risk of nasopharyngeal and conjunctival infection. 25,26 Organisms not associated with childcare, such as commensal conjunctival pathogens and enteric pathogens, were not significantly more common among females, suggesting that childcare in particular may increase the risk of conjunctival infection for females.…”
Section: Discussionmentioning
confidence: 99%
“…Young adults experience very low rates of morbidity and mortality from pneumococcal disease (e.g., 3.1 cases annually per 100,000 population versus 38.6 cases per 100,000 population in children Ͻ1 year old) (8), and their serotype-specific immunity is boosted by occasional episodes of asymptomatic colonization (33,36,37). However, in old age, a paradox emerges; while nasopharyngeal colonization appears to be less common in older adults (Table 2), they are at extremely high risk of pneumococcal disease.…”
Section: Pneumococcal Colonization and Naturally Acquired Antipneumocmentioning
confidence: 99%